The Impact of HBV Quasispecies Features on Immune Status in HBsAg+/HBsAb+ Patients With HBV Genotype C Using Next-Generation Sequencing - Wang, Ying; Xiao, Xiao; Chen, Shipeng; Huang, Chenjun; Zhou, Jun; Dai, Erhei; Li, Ya; Liu, Lijuan; Huang, Xianzhang; Gao, Zhiyuan; Wu, Chuanyong; Fang, Meng; et al. (Frontiers in Immunology, 2021)
Background: This study was aimed to explore the molecular mechanism of the coexistence of hepatitis B surface antigen (HBsAg) and hepatitis B surface antibody (HBsAb) serological pattern via intensive characterization of HBV s gene both in chronic hepatitis B (CHB) and hepatocellular carcinoma (HCC) patients. Method: A total of 73 HBsAg+/HBsAb+ patients (CHB=36, HCC=37) and 96 HBsAg+/HBsAb- patients (CHB=47, HCC=49) were enrolled from 13 medical centers in China. The sequence features were elaborated based on the combination of next-generation sequencing (NGS) and multidimensional bioinformatics analysis. Results: The 16 high-frequency missense mutations, changes of stop codon mutation, clustering and random forest models based on quasispecies features demonstrated the significant discrepancy power between HBsAg+/HBsAb+ and HBsAg+/HBsAb- in CHB and HCC respectively. The immunogenicity for cytotoxic T lymphocytes (CTL) epitope Se and antigenicity for the major hydrophilic region (MHR) were both reduced in HBsAg+/HBsAb+ patients (CTL Se:p<0.0001;MHR: p=0.0216). Different mutation patterns were observed between HBsAg+/HBsAb+ patients with CHB and with HCC. Especially, mutations in antigenic epitopes, such as I126S in CHB and I126T in HCC, could impact the conformational structure and alter the antigenicity/immunogenicity of HBsAg. Conclusion: Based on NGS and bioinformatics analysis, this study indicates for the first time that point mutations and quasispecies diversities of HBV s gene could alter the MHR antigenicity and CTL Se immunogenicity, and contribute to the concurrent of HBsAg+/HBsAb+ with different features in HCC and CHB. Our findings might renew the understanding of this special serological profile and benefit the clinical management in HBV-related diseases.